A cross-sectional study on the knowledge of knee osteoarthritis and attitude towards prevention of knee osteoarthritis in young adults - Lim, Shi Qi (2024)
Background and Objectives: Osteoarthritis (OA) is a cartilage degenerative condition that causes the joints to deteriorate, and it can attack younger individuals (mostly athletes or with joint trauma). Knee OA led to various issues and compared to the younger population, the seniors have substantially more awareness and knowledge of knee OA. This study aims to determine the knee OA knowledge level and the attitude toward knee OA prevention in young adults.